1981
DOI: 10.1523/jneurosci.01-01-00027.1981
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of neuronal and glial precursor cells in the cerebral ventricular zone of the fetal monkey: an ultrastructural immunoperoxidase analysis

Abstract: The cytological composition of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
134
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(146 citation statements)
references
References 40 publications
12
134
0
Order By: Relevance
“…In other words, most tanycytes are not PGE cells. The term "radial glia" has been applied to tanycytes that ultimately serve as proliferating progenitors of astrocytes (Levitt et al, 1981;Mission et al, 1988). The raphe p35 PGE cells seem neither to divide nor to develop into astrocytes; they are quite distinct from radial glia.…”
Section: Pge Cell Raphesmentioning
confidence: 99%
“…In other words, most tanycytes are not PGE cells. The term "radial glia" has been applied to tanycytes that ultimately serve as proliferating progenitors of astrocytes (Levitt et al, 1981;Mission et al, 1988). The raphe p35 PGE cells seem neither to divide nor to develop into astrocytes; they are quite distinct from radial glia.…”
Section: Pge Cell Raphesmentioning
confidence: 99%
“…Numerous studies have suggested that the ventricular zone (VZ) stem cells generate committed neuronal, glial, and bipotential progenitors, each restricted to the production of one or more types of postmitotic cells (Maric et al, 2000;McCarthy et al, 2001;Piper et al, 2001;Cai et al, 2002b;Liu et al, 2002;Shen et al, 2002;Maric et al, 2003;. Indeed, multipotent radial glial cells (RGCs) and distinct committed neuronal and glial progenitors have been identified in the human and monkey VZ (Levitt et al, 1981(Levitt et al, , 1983Ostenfeld and Svendsen, 2004;Zecevic, 2004). In contrast, recent reports suggest that the rodent neocortical VZ is composed primarily of multipotential RGCs, which generate all of the dorsally derived neocortical cells (Noctor et al, 2002;Fishell and Kriegstein, 2003;Weissman et al, 2003) including cortical astrocytes (Pixley and de Vellis, 1984;Misson et al, 1988;Takahashi et al, 1990;Hunter and Hatten, 1995;Kamei et al, 1998;deAzevedo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…During late stages of corticogenesis, as neurogenesis and migration dwindles, the radial glial scaffolding in the telencephalon is dismantled and transformed into type 1 astrocytes (8)(9)(10). Astrocytes contribute to the emergence and maintenance of mature brain circuitry through their function as modulators of neuronal activity (11), neurogenesis (12), and as potential neuronal precursors (13).…”
mentioning
confidence: 99%